Weak temperature and bias dependence of spin accumulation in epitaxial Co70Fe30/MgO tunnel contacts to p-type Ge - Jeon, Kun-Rok; Min, Byoung-Chul; Park, Seoung-Young (IOP PUBLISHING LTD, 2017)
Electrical spin accumulation that was robust against changes in temperature and bias voltage was achieved in epitaxial Co70Fe30/MgO tunnel contacts to p-type Ge, with negligible Schottky barrier formation. Hanle and inverted Hanle effects, which are characteristic features of non-equilibrium spin accumulation in the tunnel contacts, were clearly observed up to room temperature for both hole spin injection and extraction. Notably, the obtained spin signal showed weak temperature dependence even at a low bias voltage, and symmetric behavior with respect to bias polarity, which are inconsistent with spin-polarized tunneling via localized states in the contact. (c) 2017 The Japan Society of Applied Physics